2017
DOI: 10.18632/oncotarget.14555
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus type 16 E6 suppresses microRNA-23b expression in human cervical cancer cells through DNA methylation of the host gene C9orf3

Abstract: Oncogenic protein E6 of human papillomavirus type 16 (HPV-16) is believed to involve in the aberrant methylation in cervical cancer as it upregulates DNA methyltransferase 1 (DNMT1) through tumor suppressor p53. In addition, DNA demethylating agent induces the expression of one of the HPV-16 E6 regulated microRNAs (miRs), miR-23b, in human cervical carcinoma SiHa cells. Thus, the importance of DNA methylation and miR-23b in HPV-16 E6 associated cervical cancer development is investigated. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 51 publications
3
30
0
2
Order By: Relevance
“…It has been demonstrated that miR-23b-3p is expressed at low levels in a variety of malignant tumors, including liver cancer [18], bladder cancer [19], cervical cancer [20], colorectal cancer [21], and prostate cancer [22]. Our preliminary experiments showed that PDAC tissues and cell lines also expressed low levels of miR-23b-3p.…”
Section: Discussionmentioning
confidence: 59%
“…It has been demonstrated that miR-23b-3p is expressed at low levels in a variety of malignant tumors, including liver cancer [18], bladder cancer [19], cervical cancer [20], colorectal cancer [21], and prostate cancer [22]. Our preliminary experiments showed that PDAC tissues and cell lines also expressed low levels of miR-23b-3p.…”
Section: Discussionmentioning
confidence: 59%
“…Both HPV oncoproteins E6 and E7 have previously been shown to regulate DNA methyltransferases (60)(61)(62), but only E6 has been shown to induce hypermethylation of the IFN-promoter in keratinocytes (15). The mechanism of E6-induced hypermethylation has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of hormones, growth factors and cytokines can stimulate Akt activation, thereby regulating cell growth, proliferation, motility, invasion, apoptosis and other processes (18). Studies have indicated that phosphorylation of AKT is increased in prostate, breast and cervical cancer cells (19)(20)(21). AKT was found to induce cell proliferation and survival in β cells, endothelial cells, cardiomyocytes and tumor cells (21,22).…”
Section: Introductionmentioning
confidence: 99%